Teaching functions: Its teaching and learning at the university teacher degrees - Belletich, Olga; Wilhelmi, Miguel R. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The university teaching experience in bachelor’s teacher degrees shows that there are educational obstacles for teaching and learning of competencies associated with the teaching functions and practices required at school. the objective is to describe a didactic proposal designed expressly that allows to overcome these obstacles. it is shown that the active methodologies that grant greater autonomy in the study and that encourage inquiry, are the most pertinent to the development of this learning. the theoretical framework is based on three educational theories: theory of didactic situations; discovery learning theory and educational leadership theory.